Antibacterial activity and essential oil composition of Calendula arvensis L. - (:unkn) unknown (My University, 2020)
Essential oil composition and antibacterial activity of Calendula_x000D_ arvensis L. were investigated. The essential oil of aerial part was obtained_x000D_ through hydro-distillation using a Clevenger type apparatus with 0.38 (v/w) yield._x000D_ The essential oil components were determined by GC-MS analyses. Thirty-six_x000D_ components were identified in the essential oil that represented 91.8 % of the oil._x000D_ The major components of the essential oil were δ-cadinene (14.8 %), epi-cubebol_x000D_ (10.7 %), α-cadinol (8.5 %), cubenol (7.7 %), cubebol (7.2 %), 1-epi-cubenol (5.4_x000D_ %) and ledene (5.1 %). Antibacterial activity of essential oil was observed against_x000D_ Staphylococcus aureus ATCC 29213, Bacillus cereus ATCC 14579,_x000D_ Pseudomonas aeruginosa ATCC 27853 and Escherichia coli ATCC 25922 by_x000D_ using a broth microdilution. The essential oil showed weak inhibitory activity_x000D_ against E. coli and B. cereus at 8 mg/mL. The oil didn‘t show any antibacterial_x000D_ activity against S. aureus and P. aeruginosa. These results revealed that the oil_x000D_ was rich in oxygenated sesquiterpenes as well as had a weak antimicrobial_x000D_ activity.